Comparison and Analysis of Profitability of Top Three Nationalized Commercial Banks in Bangladesh (Global Journal of Management and Business Research, 2019)
Banks are playing a vital role in the economic & financial development of Bangladesh. Profitability indicates the overall performance of the banks. In this study, it has been tried to compare the top three nationalized commercial banks by some financial parameters, and it relies on secondary sources of data. In this paper, I used statistical tool ANOVA for comparison. The result indicates the statistical difference among these banks and their performance is not stable.
Keywords: bank; profitability; performance; ANOVA